Role of climatic factors in the toxicity of fipronil toward earthworms in two tropical soils: effects of increased temperature and reduced soil moisture content - Hennig T.B.* (2022)
© 2022, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.The aim of this study was to assess the effect of temperature on the toxicity of fipronil toward earthworms (Eisenia andrei) in two Brazilian soils (Entisol and Oxisol) with contrasting textures. In the case of Entisol, the influence of soil moisture content on toxicity was also investigated. Earthworms were exposed for 56 days to soils spiked with increasing concentrations of fipronil (8.95, 19.48, 38.22, 155.61, and 237.81 mg kg−1 for Entisol; 12.99, 27.94, 48.42, 204.67, and 374.29 mg kg−1 for Oxisol) under scenarios with different combinations of temperature (20, 25 and 27 °C) and soil moisture content (60 and 30% of water holding capacity (WHC) for Entisol and 60% WHC for Oxisol). The number of juveniles produced was taken as the endpoint, and a risk assessment was performed based on the hazard quotient (HQ). In Entisol, at 60% WHC the fipronil toxicity decreased at 27 °C compared with the other temperatures tested (EC50 = 52.58, 48.48, and 110 mg kg−1 for 20, 25, and 27 °C, respectively). In the case of Oxisol at 60% WHC, the fipronil toxicity increased at 27 °C compared with other temperatures (EC50 = 277.57, 312.87, and 39.89 mg kg−1 at 20, 25, and 27 °C, respectively). An increase in fipronil toxicity was also observed with a decrease in soil moisture content in Entisol at 27 °C (EC50 = 27.95 and 110 mg kg−1 for 30% and 60% WHC, respectively). The risk of fipronil was only significant at 27 °C in Entisol and Oxisol with water contents of 30% and 60% WHC, respectively, revealing that higher temperatures are able to increase the risk of fipronil toxicity toward earthworms depending on soil type and soil moisture content. The results reported herein show that soil properties associated with climatic shifts could enhance the ecotoxicological effects and risk of fipronil for earthworms, depending on the type of soil.